Persepsi Guru Tentang Seni Musik Terhadap Perkembangan Otak Anak Usia Dini - Azalia Arya Ramadhini; Putri Maharani; Masyunita Siregar (Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah dan Ilmu Keguruan, UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
Early childhood is a golden period of development where the early childhood brain development phase is the most important phase which covers 80% of a child's brain development. The level of brain development in children from birth to 4 years of age reaches 50%, so the first 4 years are often called the golden age. One way to develop a child's brain is through art. The research method used by researchers is a descriptive research method with a quantitative approach. The population used in this study were kindergartens in Jambi Province, namely kindergarten teachers in Jambi Province. The sample used was 6 teachers from three kindergarten schools in Jambi Province using a simple random sampling technique. The instrument used is a questionnaire / questionnaire. Data was collected using a questionnaire instrument for research subjects. Research Results 100% of respondents agree that music stimulates the brain in early childhood, have practiced movements and songs for learning. carrying out music arts activities and songs of different expression in their respective schools, children can follow the movements of the given song, children can clap their hands to the rhythm, children can follow the word pattern of the given song. The results of the respondents stated that they agreed that the art of music can improve brain development in early childhood.